Analisis Kemampuan Pemahaman Konsep Matematis Mahasiswa Program Studi PGSD - Nurkhairunnisa Siregar; Nurdiana Siregar; Hasanah Hasanah (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2020)
Describing the ability of PGSD students to understand mathematical concepts in the subject of basic mathematical concepts, as well as identifying students' difficulties in these subjects are the basic objectives of this study. This research is a qualitative research using descriptive method. 23 students of the PGSD study program were used as subjects in this study. Data collection in this study used tests and documentation. The data analysis used was descriptive qualitative analysis. The results of data analysis obtained on the average score of students' ability to understand mathematical concepts is 60.35 so that they are grouped in the sufficient category. As for the details, there are 2 students in the very good category, 6 students in the good category, and 15 students in the sufficient category. Based on the results of this study it can be concluded that the ability to understand mathematical concepts of PGSD students in the subject of basic mathematical concepts is still in the sufficient category.